Evolution and systematics of polyploid Nigritella (Orchidaceae). (30th March 2018) - Hedrén, Mikael; Lorenz, Richard; Teppner, Herwig; Dolinar, Branko; Giotta, Cesario; Griebl, Norbert; Hansson, Sven; Heidtke, Ulrich; Klein, Erich; Perazza, Giorgio; Ståhlberg, David; Surina, Boštjan
Abstract : Members of the orchid genus Nigritella are widespread in European mountains, but species circumscriptions and evolutionary patterns in the genus are subjects to conflicting opinions. We analyzed a representative material of Nigritella for differentiation at nuclear and plastid marker loci. In agreement with predictions from embryological studies, diploid members of Nigritella are sexual and mostly out‐crossing, whereas triploid, tetraploid and pentaploid members are apomicts. The diploid taxa were poorly differentiated in the investigated molecular markers, except for the western N. gabasiana, which was separated in plastid haplotypes. Polyploid Nigritella aggregate into three groups and within each of these groups apomictic polyploids have given rise to new species. Within the N. nigra group, the tetraploid N. nigra subsp. austriaca is somewhat differentiated from the triploid subsp. nigra at nuclear as well as plastid loci. Fusion of an unreduced egg cell from subsp. nigra with a haploid microgamete from Gymnadenia conopsea gave rise to Gymnigritella runei . Within the N. widderi group, N. archiducis‐joannis is poorly separated from N. widderi in molecular markers, and the pentaploid N. buschmanniae has evolved by fusion of an unreduced egg cell from N. widderi with a haploid microgamete from a diploid Nigritella . Within the N. miniata group, N. stiriaca is somewhat differentiated from N. miniata at nuclear loci, but no other segregates of N. miniata are supported at species level. Polyploid Nigritella species accumulate genetic diversity by somatic mutations. In the widespread N. nigra subsp. austriaca and N. miniata this diversity is correlated to geography. Although some polyploids may be of recent origins, each polyploid contain genetic markers no longer encountered in diploid members of the genus. According to plastid marker data, Nigritella and Gymnadenia may constitute monophyletic sister genera.